You are on page 1of 6

APPENDIX I

Derivation of the Time


Domain Solution of
State Equations
To Accompany

Control Systems Engineering


4th Edition
By
Norman S. Nise

John Wiley & Sons

Copyright 2004 by John Wiley & Sons, Inc.


All rights reserved.
No part of this publication may be reproduced, stored in a retrieval system or transmitted in
any from or by any means, electronic, mechanical, photocopying, recording, scanning or
otherwise, except as permitted under Sections 107 or 108 of the 1976 United States
Copyright Act, without either the prior written permission of the Publisher, or authorization
through payment of the appropriate per-copy fee to the Copyright Clearance Center, 222
Rosewood Drive, Danvers, MA 01923, (978) 750-8400, fax (978) 750-4470. Requests to the
Publisher for permission should be addressed to the Permissions Department, John Wiley &
Sons, Inc., 111 River Street, Hoboken, NJ 07030, (201) 748-6011, fax (201) 748-6008, email: PERMREQ@WILEY.COM. To order books please call 1 (800) 225-5945.
ISBN 0-471-44577-0
John Wiley & Sons, Inc.
111 River Street
Hoboken, NJ 07030
USA

A P P E N D I X

Derivation of the Time Domain Solution of


State Equations

I.1 Derivation
Rather than using the Laplace transformation, we can solve the equations directly in the time
domain using a method closely allied to the classical solution of differential equations. We will find
that the final solution consists of two parts that are different from the forced and natural responses
First, assume a homogeneous state equation of the form

x (t ) = Ax(t )
Since we want to solve for x, we assume a series solution, just as we did in elementary scalar
differential equations. Thus,
x(t ) = b 0 + b1t + b 2t 2 + " + bk t k + bk +1t k +1 + "

(I.1)

(I.2)

Substituting Eq. (I.2) into (I.1) we get


b1 + 2b 2t + " + kbk t k 1 + (k + 1)bk +1t k + "
=A(b 0 + b1t + b 2t 2 + " + bk t k + bk +1t k +1 + ")

(I.3)

Equating like coefficients yields


b1 = Ab 0
1
1
b 2 = Ab1 = A 2b 0
2
2
#
1
bk = A k b0
k!
1
bk +1 =
A k +1b 0
(k + 1)!
#
Substituting these values into Eq. (I.2) yields

(I.4a)
(I.4b)

(I.4c)
(I.4d)

Appendix I Derivation of the Time Domain Solution of State Equations

1
1
1
x(t ) = b 0 + Ab 0t + A 2b 0t 2 + " + A k b 0t k +
A k +1b 0t k +1 + "
2
k!
(k + 1)!

1
1
1
A k +1t k +1 + " b 0
= I + At + A 2t 2 + " + A k t k +
k!
2
(k + 1)!

(I.5)

But, from Eq. (I.2),


x(0) = b 0

(I.6)1

Therefore,

1
1
1
x(t ) = I + At + A 2t 2 + " + A k t k +
A k +1t k +1 + " x(0)
2
(k + 1)!
k!

(I.7)

Let

1
1
1
e At = I + At + A 2t 2 + " + A k t k +
A k +1t k +1 + "
k!
2
(k + 1)!

(I.8)

where e At is simply a notation for the matrix formed by the right-hand side of Eq. (I.8). We use this
definition because the right-hand side of Eq. (I.8) resembles a power series expansion of e at , or

1
1
1
e at = 1 + at + a 2t 2 + " + a k t k +
a k +1t k +1 + "
2
(k + 1)!
k!

(I.9)

Using Eq. (I.7), we have


x(t ) = e At x(0)

(I.10)

We give a special name to e At : it is called the state-transition matrix2,since it performs a


transformation on x(0) , taking x from the initial state, x(0) , to the state x(t ) at any time, t. The
symbol, (t ) , is used to denote e At . Thus,

In this development we consider the initial time, t0 , to be 0. More generally, t0 0 . After completing this

development, the interested reader should consult Appendix J on the accompanying CD-ROM for the more general
solution in terms of initial time t0 0 .
2

The state-transition matrix here is for the initial time t0 = 0 . The derivation in Appendix J on the accompanying CD-

ROM for t0 0 yields x(t ) = e

A ( t t0 )

x(t0 ) .

I.1 Derivation

(t ) = e At

(I.11)

and
x(t ) = (t )x(0)

(I.12)

There are some properties of (t ) that we will use later when we solve for x(t ) in the text.
From Eq. (I.12),
x(0) = (0)x(0)

(I.13)

Hence, the first property of (t ) is


(0) = I

(I.14)

where I is the identity matrix. Also, differentiating Eq. (I.12) and setting this equal to Eq. (I.1)
yields
 (t ) x(0) = Ax(t )
x (t ) =

(I.15)

 (0) x(0) = Ax(0)

(I.16)

which, at t = 0 , yields

Thus, the second property of (t ) follows from Eq. (I.16):


 (0) = A

(I.17)

In summary, the solution to the homogeneous, or unforced, system is


x(t ) = (t ) x(0)

(I.18)

where
(0) = I

(I.19)

 (0) = A

(I.20)

and

Let us now solve the forced, or nonhomogeneous, problem. Given the forced state equation
x (t ) = Ax(t ) + Bu (t )

(I.21)

Appendix I Derivation of the Time Domain Solution of State Equations

rearrange and multiply both sides by e At :


e At [ x (t ) Ax(t )] = e At Bu(t )

(I.22)

Realizing that the left-hand side is equal to the derivative of the product e At x(t ) , we obtain
d At
[e x(t )] = e t Bu(t )
dt

(I.23)

Integrating both sides yields


t

[e At x(t )] = e t x(t ) x(0) = e Bu ( ) d

(I.24)

since e At evaluated at t = 0 is the identity matrix (from Eq. (I.8)). Solving for x(t ) in Eq. (I.24) we
obtain
x(t ) = e t x(0) +

e
0

( t )

Bu ( ) d

= (t ) x(0) +

(t )Bu( )d
0

(I.25)

where (t ) = e At by definition.

Bibliography
Timothy, L. K., and Bona, B. E. State Space Analysis: An Introduction. McGraw-Hill, New York,
1968.

You might also like